Comparison of bridge design in Malaysia between American codes and British codes - Wan Ahmad Kamal, Wan Ikram Wajdee (2005)
The design of a highway bridge, like most any other civil engineering project, is dependant on certain standards and criteria. Naturally, the critical importance of highway bridges in a modern transportation system would imply a set of rigorous design specifications to ensure the safety and overall quality of the constructed project. By general specifications, we imply an overall design code covering the majority of structures in a given transportation system.In the United States bridge engineers use AASHTO’s standard Specification for Highway Bridges and, in similar fashion or trends, German bridge engineer utilize the DIN standard and British and Malaysia designers the BS 5400 code. In general, countries like German and United Kingdom which have developed and maintained major highway systems for a great many years possess their own national bridge standards. The AASHTO Standard Specification, however, have been accepted by many countries as the general code by which bridges should be designed. In this research study, investigation and comparisons using codes of practices for bridge design in Malaysia is done . American codes has been choosen as an alternative to British codes in design of bridge, followed by comparison in term of structure component performance due to seismic loading. The purpose is to investigate the performance of existing bridge in Malaysia due to seismic resistant. Thus, the bridge performance over the safety condition and structure integrity while using both codes of practices, American and British Codes is identified.